La criminalística como ciencia auxiliar esencial en la resolución de casos de macrocriminalidad como los cometidos por las bacrim en Colombia el caso del homicidio del informante de sandoná (2014)
The main goal of this study is aimed to describe hoy the procedures and elements used in criminalistics are essential to solve a specific case. In particular this work intends to show how the finding of the causes and circumstances of time, mode and place of a punishable conduct, with the tools and inputs that criminal science provides can lead to establish the causes of the crime and its authors, so the ease can be delimited and connected with others, having in mind specific contexts, relevant in macro criminality such as that commited by armed illegal groups, such as so-called bacrim in Colombia. Furthermore, this work intends to show how is that the commission of a crime such as homicide and torture are the main infractions to criminal law committed by these groups with the purpose to silence the civil population, instilling fear, forwhich the case analysis is useful as long as the parameters of the case individually considered are links with others and then mixed within a generalized context that allows, in that way, to combat impunity